A Transient Receptor Potential Ion Channel in Chlamydomonas Shares Key Features with Sensory Transduction-Associated TRP Channels in Mammals. Issue 1 (16th January 2015) - Arias-Darraz, Luis; Cabezas, Deny; Colenso, Charlotte K.; Alegría-Arcos, Melissa; Bravo-Moraga, Felipe; Varas-Concha, Ignacio; Almonacid, Daniel E.; Madrid, Rodolfo; Brauchi, Sebastian
Abstract : A transient receptor potential channel from a green alga shares key features with its mammalian counterparts, suggesting that its basic characteristics evolved early in eukaryotic history. Abstract: Sensory modalities are essential for navigating through an ever-changing environment. From insects to mammals, transient receptor potential (TRP) channels are known mediators for cellular sensing. Chlamydomonas reinhardtii is a motile single-celled freshwater green alga that is guided by photosensory, mechanosensory, and chemosensory cues. In this type of alga, sensory input is first detected by membrane receptors located in the cell body and then transduced to the beating cilia by membrane depolarization. Although TRP channels seem to be absent in plants, C. reinhardtii possesses genomic sequences encoding TRP proteins. Here, we describe the cloning and characterization of a C. reinhardtii version of a TRP channel sharing key features present in mammalian TRP channels associated with sensory transduction. In silico sequence-structure analysis unveiled the modular design of TRP channels, and electrophysiological experiments conducted on Human Embryonic Kidney-293T cells expressing the Cr-TRP1 clone showed that many of the core functional features of metazoan TRP channels are present in Cr-TRP1, suggesting that basic TRP channel gating characteristics evolved early in the history of eukaryotes.